2014
DOI: 10.1089/adt.2014.595
|View full text |Cite
|
Sign up to set email alerts
|

Assessing HTS Performance Using BioAssay Ontology: Screening and Analysis of a Bacterial Phospho-N-Acetylmuramoyl-Pentapeptide Translocase Campaign

Abstract: With the public availability of biochemical assays and screening data constantly increasing, new applications for data mining and method analysis are evolving in parallel. One example is BioAssay Ontology (BAO) for systematic classification of assays based on screening setup and metadata annotations. In this article we report a high-throughput screening (HTS) against phospho-N-acetylmuramoyl-pentapeptide translocase (MraY), an attractive antibacterial drug target involved in peptidoglycan synthesis. The screen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Together, these studies provide the proof‐of‐concept for our approach, and pave the way for increasing the potency and specificity for diverse monotpic PGTs and potentially the more complex polytopic PGTs by performing structure optimization at the diverse point of contact with the enzyme. Of paramount importance in these studies was the establishment of a reproducible enzyme purification protocol, and the development of a reliable activity assay, which in contrast to existing fluorescence‐based assays for MraY, represents a significant challenge. We found that both assays described herein report accurately on PglC activity.…”
Section: Resultsmentioning
confidence: 99%
“…Together, these studies provide the proof‐of‐concept for our approach, and pave the way for increasing the potency and specificity for diverse monotpic PGTs and potentially the more complex polytopic PGTs by performing structure optimization at the diverse point of contact with the enzyme. Of paramount importance in these studies was the establishment of a reproducible enzyme purification protocol, and the development of a reliable activity assay, which in contrast to existing fluorescence‐based assays for MraY, represents a significant challenge. We found that both assays described herein report accurately on PglC activity.…”
Section: Resultsmentioning
confidence: 99%
“…PGTs represent important targets for inhibitor design due to their centrality in bacterial glycan synthesis. Except for MraY, for which a high-throughput fluorescent assay has been developed 28 , advances in inhibitor development for the PGTs that transfer simple sugar phosphate moieties have been hampered by the traditional challenging and cumbersome kinetic assays discussed above. The 96-well plate-based format makes the UMP-Glo assay highly attractive for inhibitor screening.…”
Section: Resultsmentioning
confidence: 99%
“…They extracted metrics on the utilization of assay design and detection approaches and considered over-vs. underutilization of potential technologies. BAO terms were also used to identify similar assays from which hits were acknowledged as frequent false-positive results in high-throughput screening (Moberg et al 2014;Schürer et al 2011).…”
Section: Applications Of the Bao To Bioassay Databasesmentioning
confidence: 99%